THE IMPACT OF DIGITALIZATION ON THE GROWTH OF MSMES IN THE MODERN ECONOMY - Triyani Capeg Hadmandho; Sri Isfantin Puji Lestari; Loso Judijanto (Adisam Publisher, 2025)
Digitalization has become the main catalyst in spurring the growth of Micro, Small and Medium Enterprises (MSMEs) in the modern economic era. This literature research examines the various impacts that digitalization has on the growth of MSMEs. Among other things, digitalization significantly increases operational efficiency through automation of business processes such as inventory management, accounting and customer service. In addition, digital technology opens up MSME access to a wider market through e-commerce and digital marketing platforms, enabling them to reach global customers and increase sales. Digitalization also plays an important role in improving the quality of customer service through personalization of service and more effective communication. Customer Relationship Management (CRM) tools and data analytics help MSMEs understand customer needs and develop better service strategies. Fintech and crowdfunding platforms offer more accessible alternative financing options, supporting the expansion and growth of MSME businesses. Product and service innovation is driven by digital technology, enabling MSMEs to remain competitive and responsive to changing market needs. Additionally, digital platforms facilitate collaboration and networking, supporting a more efficient exchange of knowledge and resources. Overall, digitalization not only accelerates the growth of MSMEs but also strengthens the economy as a whole by opening up new opportunities and optimizing existing potential.